Ta’līmu al-Kitābi al-Aṣfari Fī al-‘Aṣri al-Ḥadīṡ (Ta’līmu Qawāidi al-Lugati al-Arabiyyati bi Kitābi Alfiyyah ibn Mālik Fī Faṣli Alfiyyah Ṡāniyah Bi Ma’hadi Al-Luqmāniyyah al-Islāmiy as-Salafiy Yogyakarta) - Didin Rojudin; Mohammad Zaelani Musonif (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2022)
In reality, learning Arabic grammar is seen as something difficult because of the complexity of the nahwu and ṣaraf. This study aims to describe learning design models, processes, supporting andinhibiting factors in learning Arabic grammar using the Alfiyyah ibn Mālik in Alfiyyah II class at al-Luqmaniyyah Islamic Boarding School, Yogyakarta. This research is included in the qualitative research which is descriptive analysis. Data obtained through interviews, observation, and documentation. Data analysis is done by reduction, presentation, and conclusion. The validity of the data is done through source triangulation techniques. The result of this research is the learning design model used is an active learning model and a behavioral system learning model that focuses on students with presentation, discussion, question and answer, lecture, memorization, and bandongan methods. The learning process has three stages, with a learning process that is centered on students and the innovation of obligatory questioners and obligatory answerers in learning. Internal supporting factors includelove for nahwu science, students' interest in learning nahwu, preparation before entering class, high motivation, and ustāż competence. External supporting factor covers learning system centered on students, friends who invite discussion, learning outside the classroom, punishment and munāqosyah Alfiyyah ibn Mālik. Internal inhibiting factor covers the diversity of students' abilities, unpreparedness before entering class, laziness, low knowledge of nahwu, and lack of self-confidence. External inhibiting factorscoversInsufficient time allocation, clashes between Islamic boarding schools and campus activities, difficult materials, methods that are not suitable for students, and mufrodat. Keywords: Grammar, Islamic Boarding School, Learning ملخص يعتبر تعليم قواعد اللغة العربية في الواقع بأمر صعب بسبب تعقيدات علم النحو والصرف. هدف هذا اللبحث وصف تصميم النماذج والعمليات والعوامل الداعمة والمثبطة لتعليم قواعد اللغة العربية باستخدام كتاب ألفية بن مالك في فصل ألفية الثانية بمعهد اللقمانية الإسلامي السلفي يوكياكرتا. هذا البحث من ضمن البحث النوعي وهو تحليل وصفي بطبيعته . حصلت البيانات من المقابلات والملاحظة والدراسة التوثيقة . تحليل البيانات يقام بطريق الاختزال والعرض والاستنتاج. وتم تحقق صحة البيانات بطريقة تثليث المصادر. أما النتائج على الشكل التالى: تصميم نماذج التعليم المستخدمة في التعليم التعلم النشط و النظام السلوكي الذي يركز على الطلاب من خلال العرض والمناقشة والسؤال والجواب والمحاضرة ونظام الحفظ وباندونغان. تتكون عملية التعليم من ثلاث مراحل تتركز على الطلاب وهناك عملية ابتكارية وهي أسئلة إلزامية وإجابات إلزامية في التعليم . العوامل الداعمة الداخلية للتعليم وهي حب علم النحو ورغبة الطلاب في تعلم النحو ووجود الاستعداد قبل دخول الفصل والدافع العالي وكفاءة المعلم. والعوامل الداعمة الخارجية له هي نظام تعليمي يرتكز على الطلاب والأصدقاء الذين يدعون للمناقشة والتعلم الإضافي خارج الفصل والعقاب وامتحان المناقشة لألفية بن مالك. العوامل المثبطة الداخلية للتعليم هي تنوع قدرات الطلاب وعدم الاستعداد قبل دخول الفصل والكسل ، وقلة المعرفة بعلم النحو وانعدام الثقة بالنفس. العوامل المثبطة الخارجية للتعليم هي نقص توزيع الوقت واشتباك الأنشطة بين المعهد والجامعة وصعوبة المواد وعدم موافقة الطلاب بالطريقة والمفردات . الكلمات الرئيسية: التعليم، القواعد، المعهد الإسلامي